The Gibbons New Perspectives on Small Ape Socioecology and Population Biology - Whittaker, Danielle; Lappan, Susan; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
The small apes, or gibbons, are among our closest living relatives, yet they have received little attention from the scientific community and the public in comparison with the other living apes. This oversight is not due to lack of appeal; their physical beauty, graceful acrobatic movements, and thrilling songs make it clear why gibbons are always among the most popular animals in zoos. Rather, the inherent difficulties involved in studying or filming gibbons in their natural habitats and, in some cases, the misconception that among apes, smaller means lesser, have led many researchers and filmmakers to focus their attentions elsewhere. Nonetheless, a growing number of intrepid field and laboratory researchers have made steady progress in the study of gibbon behavior and ecology over the last several decades. This volume is a systematic compilation of recent research on gibbon socioecology and population biology with a focus on understanding gibbons in the context of their natural habitats, and includes contributions on a range of topics, including gibbon biogeography, the ecological roles played by gibbons in their ecosystems, the origins and functions of key gibbon social and ecological adaptations, and the conservation status of wild gibbon populations. The contributors address both theoretical questions and the practical implications of our growing knowledge about gibbon adaptations. While gibbons share several important social features with humans, thus providing parallels for understanding human evolution, they are also fascinating creatures in their own right and act as vital components of tropical forest ecosystems. Unfortunately, gibbons are also among the most endangered living apes. This volume should be of interest to researchers and students from a variety of fields, including anthropologists, animal behaviorists, tropical ecologists, evolutionary biologists, and conservation biologists.
The Diversity of Small Apes and the Importance of Population-Level Studies -- Biogeography -- Evolutionary Relationships Among the Gibbons: A Biogeographic Perspective -- Genetic Differentiation of Agile Gibbons Between Sumatra and Kalimantan in Indonesia -- Vocal Diversity of Kloss's Gibbons (Hylobates Klossii) in the Mentawai Islands, Indonesia -- Phylogeography of Kloss's Gibbon (Hylobates Klossii) Populations and Implications for Conservation Planning in the Mentawai Islands -- Individual and Geographical Variability in the Songs of Wild Silvery Gibbons (Hylobates Moloch) on Java, Indonesia -- The Fossil Record of Gibbons -- Diet and Community Ecology -- Hylobatid Diets Revisited: The Importance of Body Mass, Fruit Availability, and Interspecific Competition -- Competition and Niche Overlap Between Gibbons (Hylobates albibarbis) and Other Frugivorous Vertebrates in Gunung Palung National Park, West Kalimantan, Indonesia -- The Seed Dispersal Niche of Gibbons in Bornean Dipterocarp Forests -- The Relationship Between Ecology and Social Organization -- Ecology and the Social System of Gibbons -- The Ecology and Evolution of Hylobatid Communities: Causal and Contextual Factors Underlying Inter- and Intraspecific Variation -- Seasonal Home Range Use and Defendability in White-Handed Gibbons (Hylobates lar) in Khao Yai National Park, Thailand -- Mating Systems and Reproduction -- Monogamy in Mammals: Expanding the Perspective on Hylobatid Mating Systems -- Monitoring Female Reproductive Status in White-Handed Gibbons (Hylobates lar) Using Fecal Hormone Analysis and Patterns of Genital Skin Swellings -- Patterns of Infant Care in Wild Siamangs (Symphalangus syndactylus) in Southern Sumatra -- The Social Organization and Mating System of Khao Yai White-Handed Gibbons: 1992-2006 -- Conservation Biology -- Status and Conservation of Yellow-Cheeked Crested Gibbons (Nomascus gabriellae) in the Seima Biodiversity Conservation Area, Mondulkiri Province, Cambodia -- The Distribution and Abundance of Hoolock Gibbons in India -- Census of Eastern Hoolock Gibbons (Hoolock leuconedys) in Mahamyaing Wildlife Sanctuary, Sagaing Division, Myanmar -- The Population Distribution and Abundance of Siamangs (Symphalangus syndactylus) and Agile Gibbons (Hylobates agilis) in West Central Sumatra, Indonesia -- Canopy Bridges: An Effective Conservation Tactic for Supporting Gibbon Populations in Forest Fragments -- The Role of Reintroduction in Gibbon Conservation: Opportunities and Challenges -- Saving the Small Apes: Conservation Assessment of Gibbon Species at the 2006 Asian Primate Red List Workshop.
Keywords: LIFE SCIENCES; ZOOLOGY; LIFE SCIENCES; ZOOLOGY